2020
DOI: 10.1177/0961000620925547
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ attitudes and perceptions towards the effectiveness of mobile learning: A comparative information-need perspective

Abstract: The rapid development of information and communication technologies has revolutionized the lifestyles and learning practices of the younger population worldwide. Various new mobile platforms and forms of social media have been so pervasive and influential in the world of higher education that they have contributed much to the training of the next generation of medical professionals. As such, the current study aimed to compare the adoption of mobile learning amongst three groups of medical science students at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…Some studies have started to investigate the effect of quality measurements on the usability of mobile learning, specifically during COVID-19. These studies confirmed that quality measurements might support the discovery of quality aspects important to ensuring the actual usage of mobile learning applications [59][60][61][62][63]. As a result, these studies have recommended that quality measurements play a critical role in improving the quality of numerous kinds of educational applications, such as learning management systems, e-learning systems and mobile learning applications [59][60][61][62][63].…”
Section: Literature Review and Research Backgroundsupporting
confidence: 54%
“…Some studies have started to investigate the effect of quality measurements on the usability of mobile learning, specifically during COVID-19. These studies confirmed that quality measurements might support the discovery of quality aspects important to ensuring the actual usage of mobile learning applications [59][60][61][62][63]. As a result, these studies have recommended that quality measurements play a critical role in improving the quality of numerous kinds of educational applications, such as learning management systems, e-learning systems and mobile learning applications [59][60][61][62][63].…”
Section: Literature Review and Research Backgroundsupporting
confidence: 54%
“…Students' responses to the four themes' items explained that the road of benefitting from mobile technology in their university study is almost paved which consistent with Huang (2014). Moreover, Zhang et al (2020) confirmed that university students tend to have more diverse information needs and use their mobiles in various learning related activities. Students in the study showed their capabilities to use this technology, as they could learn new applications on individual bases, they are willing to follow-up technology updates and they continued using mobile applications independently which is partially consistent with the study of Lai and Hong (2015).…”
Section: Discussionmentioning
confidence: 71%
“…Notably, clinical science and nursing students had similar perceptions and behavior, and tended to have more varied information needs. On the other hand, Chinese respondents studying medicine were not as active in their use of mobile devices for learning as the other two majors [14].…”
Section: Literature Reviewmentioning
confidence: 95%
“…Research shows that the majority of students used mobile devices for accessing various social networks, recreation and entertainment [14]. The small screen size, entertainment, and privacy aspect prevented them from participating in formal learning activities with the same frequency as they did for entertainment purposes.…”
Section: Literature Reviewmentioning
confidence: 99%